Analysing Liquidity, Credit Risk and Deposit Money Banks Profitability in Nigeria - Minh, Hieu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examined the impact of liquidity and credit risk on profitability of selected deposit money banks(DMBs) in Nigeria. The study adopts an empirical longitudinal research design and used data set covering 7-year period from 2012 to 2018 from the annual reports of five DMBs. Pearson Correlation and multiple regression techniques were used in empirical analysis and testing of hypotheses. The result shows that there is a significant relationship between liquidity and profitability measured as return on equity (ROE). There is an insignificant relationship between credit risk variables and profitability (ROE). The paper recommends that optimal level of liquidity should be maintained to reduce cash sterility in the assets of banks. Though credit risk is not a main determinant of bank profitability; effective strategies should be put in place to monitor, control and manage credit risk.